A curious case of herbivory in the common toad Rhinella arenarum arenarum during hibernation in captivity conditions - Jungblut, Lucas David (2013)
The common toad Rhinella arenarum arenarum is used in our laboratory for teaching and research, studying different aspects of the anuran development. Hormonally induced adults allow us to obtain embryos by in vitro fertilization throughout the year. However, adult toads hibernate during nonbreeding season (March-August) making it very hard to find them in nature (Gallardo, 1958). Consequently, we usually maintain captive breeding pairs after breeding season, inducing an “artificial winter” in the laboratory. The finding described in this note was observed on August 2012 in a group of animals that came out of their artificial hibernation.